Relationship between Toxic Leadership and Job Stress of Knowledge Workers - Hadadian Zagross; Zarei Jamileh (Studies in Business and Economics, 2016)
Nowadays, different levels of stress and nervousness can be found in organizations. Owing to the fact that employees spend most of their time in organizations, stress may affect the health of employees. Hence, study of stress and the factors that make stress can be a viable decision in that by eliminating these factors organizations can have healthier employees. This study is a correlation study which aims to determine the possible relationship between toxic leadership and job stress. Data collection tools including two standard questionnaires were used. The questionnaire adopted from toxic leadership (Schmidt and Hanges 2009) to measure the toxic leadership in organizations and the NIOSH Generic Job Stress Questionnaire (Hurrell and McLaney 1988) to measure the job stress. In order to analyze the data SPSS software was used. Results show that there is a significant direct relationship between toxic leadership and the job stress of employees. In other words, the more toxic leadership perceived by employees, the more job stress they feel.